Current issues in intercultural pragmatics - Kecskés, István; Assimakopoulos, Stavros (Pragmatics & beyond, 2017)
Intro -- Current Issues in Intercultural Pragmatics -- Editorial page -- Title page -- LCC data -- Table of contents -- Introduction -- References -- Chapter 2. "Western" Grice?: Lying in a cross-cultural dimension -- 1. Introduction -- 2. A general definition of lying -- 3. Investigating lying from a cross-cultural perspective -- 3.1 Standard situations of lying -- 3.2 Values associated with lying -- 4. Is the Gricean approach ethnocentric? -- 5. Conclusions -- References -- Chapter 3. Why is miscommunication more common in everyday life than in lingua franca conversation? -- 1. Introduction -- 2. The mental worlds of communicants -- 3. Features of everyday and lingua franca conversation -- 3.1 Everyday conversation -- 3.2 Lingua franca conversation -- 4. Process of communication -- 4.1 The starting point: What the Speaker wants to say -- 4.2 Which Form will be chosen for the Meaning? -- 4.3 What happens when articulating the utterance? -- 4.4 Does the utterance reach the Recipient? -- 4.5 Failures in the interpretation of Meaning -- 4.6 Misreference -- 5. Conclusion -- References -- Chapter 4. "Burn the antifa traitors at the stake…": Transnational political cyber-exchanges, proximisation of emotions -- 1. Introduction -- 2. Theoretical considerations -- 2.1 Ideological common ground defining far-right discourse -- 2.2 Salience of lexical units defining axiological values of far-right discourse -- 2.2 Salience of lexical units defining axiological values of far-right discourse -- 2.3 Cyber communication context: Proximising a threat -- 3. Data, typology, methodology -- 3.1 Data -- 3.2 Methodology -- 4. Analysis of avatars and pseudonyms -- 4.1 Quantitative results -- 4.2 Proximisation of positive emotions towards the Self -- 4.3 Proximisation of negative emotions towards the Other.
Keywords: Aufsatzsammlung; Pragmatik; Kulturkontakt